Muhammadiyah Education Social Movement West Kalimantan - Amalia Irfani,; Syamsul Arifin,; Machmud, Muslimin; Hidayat, Samsul (Technium Social Sciences Journal, 2023)
This study aims to see the extent to which the educational social movement carried out by the West Kalimantan Muhammadiyah Association makes it worthy of being called a progressive Islamic movement. As a large organization, Muhammadiyah actively contributes to regional development, creates jobs, educates people to be intelligent and cultured without ever questioning the differences that appear. Research on ethnographic studies using the theory of resource mobilization resulted in the finding that the Muhammadiyah social movement in West Kalimantan was originally a form of need, anxiety within the individual before finally giving rise to social concern and becoming an identity movement. As a meaningful action, Muhammadiyah's educational social movement also took part contributing to maintaining harmony, by spreading militant cadres in various regional religious institutions and organizations.